The Intersection of Creativity and Technology in Visual Arts: Implications for Fashion Photography in Malaysia - Siti Shahida, Kamel; Siti Rohaya, Yahaya (2025)
This conceptual paper explores the developing connection between creativity and technology in visual arts, emphasizing its implications for fashion photography. It analyses the influence of technological advancements, including digital tools and platforms, on the creative processes in photography, modifying the understanding, creation, and use of visual storytelling. This study proposes a framework for understanding creativity as a multidimensional construct influenced by cultural, emotional, and technological factors by outlining relevant literature. This paper discusses how these technological advances can elevate audience engagement, enhance brand identity, and address specific obstacles in the Malaysian fashion industry. By incorporating theoretical perspectives with practical insights, the findings broaden the discourse on creativity in the arts by establishing how components such as the usage of digital tools and platforms can be strategically integrated into fashion photography practices. This study provides a basis for further investigation into the implications of creativity and technology on the future direction of commerce, especially in developing economies.